Cytoprotective effect and antioxidant activities of hesperidin against cisplatin-induced fibroblast cell - Anif Nur Artanti; Fea Prihapsara; Faaza Aulia Rahman; Mukh Syaifudin; Muchtaridi Muchtaridi; Endah Puji Septisetyani; Edy Meiyanto; Okid Parama Astirin (Journal of Advanced Pharmaceutical Technology & Research)
Cisplatin (Cisp), a platinum-based compound, is a potent chemotherapy drug that effectively treats various cancers such as lung, breast, bladder, and hepatocellular carcinoma. However, its clinical application is limited due to its fibroblast damage, which is linked to its ability to produce collagen and other extracellular matrix components essential for tissue healing. Enhancing antioxidant capacity offers a potential strategy to reduce Cisp-induced fibroblast damage. Hesperidin (HSD), a flavonoid from Citrus sp., exhibits various pharmacological properties, including anti-inflammatory and antioxidant effects. This study aims to determine HSD as cytoprotective induced by Cisp using the fibroblast cell lines (NIH-3T3). 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay was used to determine antioxidant activity. The viability cell after treatment with HSD, Cisp, and cotreatment HSD-Cisp was evaluated through Mictroculure Tetrazolium Technique (MTT) assay. The evaluation of senescence was performed using the senescence-associated β-galactosidase assay. Gelatin zymography assay was utilized to analyze the activity of matrix metalloproteinases (MMPs). Data were analyzed using one-way ANOVA and Tukey’s post hoc test in SPSS (version 20.0). The IC50 of the radical scavenging assay of HSD was found to be 20.967 ± 0.016 µM. HSD showed low cytotoxicity against NIH-3T3 cells, with IC50 values of over 500 µM. HSD showed an antagonistic effect when used as cotreatment HSD with Cisp in NIH-3T3 cells, with a combination index >1. Cotreatment of HSD and Cisp reduces cellular senescence and the expression of MMP-9 and MMP-2. These findings suggest that HSD could be beneficial as a cytoprotective agent, helping to maintain cellular health against chemotherapy.